Nanotechnology within the legal and regulatory framework: An introductory overview - Karim, M.E. (Lexis Nexis, 2014)
Nanotechnology, often referred to as the next industrial revolution after the internet, is an interdisciplinary study and the wave of the future. It is the science of manipulating technology at an atomic and molecular scale and is no longer an issue for scientists only. It has limitless potential and can be used in most areas of human need. Based on very optimistic results in many scientific researches around the world, it can easily be inferred that its limitless promises will bring epoch making changes in the world very soon. There are already over 2,000 consumer products in the market which are developed containing nanoparticle and that use nanotechnology. However, there are also concerns as there are many who consider nanoparticles as the next asbestos and are reluctant to welcome nanotechnology with an open mind. This is a matter of great concern that the global community is still in search of a consensus on legal and regulatory frameworks to govern it. As of now, there are many areas i.e. product safety, privacy and civil liberties, occupational health and safety ('OH&S'), intellectual property ('IP'), international law, environmental law, law of insurance, law of customs, consumer protection and waste management which are directly related to nanotechnology research, development and commercialisation, and the law must intervene in these areas. While the benefits that can be achieved by using nanotechnology are whole-heartedly welcomed and appreciated, this paper aims at introducing the legal aspects of nanotechnology with an appeal that the development of nanotechnology should be regulated properly and the scientist must not be given a blank cheque in their hands to make experiments that may create adverse effects. The mistakes which halted the introduction and commercialisation of genetically modified food or nuclear energy should not be repeated and the application of nanotechnology should be encouraged within the approved legal framework.